Land Use Analysis of Central Business District (CBD) of Metropolis Saddar Karachi through SRS/GIS Techniques - Kausar, Anila; Afsar, Sheeba; Wazir, Zohra; Lahori, Altaf Hussain; Afzal, Ambreen; Arif, Junaid; Sydorenko, Volodymyr; Pruskyi, Andrii; Tyshchenko, Vasyl (Ecological Questions, 2022)
The high density of buildings and roads are commonly associated with the Central Business District (CBD) of a metropolitan and multicultural city Karachi, Pakistan. It is the highly interactive place of a metropolis, therefore, considers functionally effective zones. This paper will prove even with a high rate of urbanization and expansion due to urban sprawl, still Saddar is the focus of attraction concerning several facts. The main objectives of the study were to explore the land-based cataloging of Saddar based on activity and to assess the environmental issues which are associated with this land use classification for the sustainability of CBD the people perception methods of identification of research, Land-use (LU) Analysis of Area of Interest (AOI) via, questionnaire-based surveying, and geo-coding of activities methods have been used in this study. The obtained results revealed that Saddar town covers land use approximately, 4.28% Leisure, 9.38% Shopping, Business or Trade, 7.9% Social, Institutional, or Infrastructure Related, 4.62% Mass Assembly of People, 6.37% Industrial, Manufacturing, and Waste Related, while 5.68% Traveler Movement,5.9% Natural Resource Related,52.40% Residential,3.4% No Human Activity or Unclassified. Approximately, 44.2% of the land use was engaged in capita producing activities, which reflects CBD’s functional strength. Overall, it recommended that there should be more green spaces in the CBD to improve air quality. Vertical urban gardening/forest can be implemented as Saddar has limited space and it is a concrete jungle having very less open space.